2012
DOI: 10.1007/s00467-012-2194-9
|View full text |Cite
|
Sign up to set email alerts
|

Dental calculus formation in children and adolescents undergoing hemodialysis

Abstract: In conclusion, patients undergoing hemodialysis presented accelerated dental calculus formation, probably due to salivary variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 20 publications
4
26
0
14
Order By: Relevance
“…This finding also emphasized the key role of P in dental calculus formation [8]. A previous study also showed that only the P concentration in stimulated whole saliva was associated with dental calculus formation, corroborating the findings of Epstein et al, who found that elevated levels of P and protein may contribute to dental calculus formation [17]. More P is secreted in saliva because of renal function deterioration, and severe RRF may have resulted in the greater amount of dental calculus formation in the HD group.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding also emphasized the key role of P in dental calculus formation [8]. A previous study also showed that only the P concentration in stimulated whole saliva was associated with dental calculus formation, corroborating the findings of Epstein et al, who found that elevated levels of P and protein may contribute to dental calculus formation [17]. More P is secreted in saliva because of renal function deterioration, and severe RRF may have resulted in the greater amount of dental calculus formation in the HD group.…”
Section: Discussionsupporting
confidence: 78%
“…The consequence is increased synthesis and secretion of the parathyroid hormone (secondary hyperparathyroidism), which causes low levels of Ca in the HD group [16]. The higher levels of Ca in PD patients may also be related to their higher dietary Ca intake and supplementation that they are recommended [17].…”
Section: Discussionmentioning
confidence: 99%
“…They are also able to produce 10-to 50-fold greater salivary urea levels than healthy subjects. 29,35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though, no significant statistical difference between groups regarding plaque was reported by Abdellatif et al (6) and Martins et al (34), which is probably due to the similar socio-economic levels and oral hygiene neglect by both groups or due to the effect of salivary uraemia and its inhibitory effect on plaque formation in the renal group.…”
Section: Discussionmentioning
confidence: 77%